Pengaruh Kepercayaan Dan Kemudahan Transaksi Terhadap Keputusan Pembelian Online Pada Marketplace Shopee Di Kota Surabaya (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2022)
ABSTRACT The purpose of this study was to analyze and determine the influence of trust and ease of transactions on the decision to online purchasing at the Shopee marketplace in the city of Surabaya both simultaneously and partially and to determine the dominant variables on online purchasing decisions. This research is a quantitative research with causal research type. The population used in this study are all Shopee users who have purchased products in the city of Surabaya, the number of samples is 100 respondents who have been distributed through questionnaires. This study uses a probability sampling technique with a simple random sampling approach in determining the sample because the population of this study is unknown. The data sources of this research are primary data and secondary data. The data analysis technique in this study used an instrument test, classical assumption test, multiple linear regression analysis test, simultaneous test, partial test, and the coefficient of determination test. The data was statistically processed with the SPSS 25 program. The results of this study indicate that trust and ease of transactions simultaneously affect online purchasing decisions at the Shopee marketplace in the city of Surabaya, and the trust and ease of transactions partially affect online purchasing decisions at the Shopee marketplace in the city of Surabaya. The trust variable is a variable that influences online purchasing decisions at the Shopee marketplace in the city of Surabaya.